Фізичне моделювання впливу фракційного складу зважених часток на теплопередачу від палаючого факела в сталеплавильних агрегатах - Молчанов, Л. С.; Голуб, Т. С.; Синегін, Є. В.; Семикін, С. І. (Physico-technological Institute of Metals and Alloys, 2023)
In the conditions of the top oxygen-converter blowing the possibility of postcombustion of the exhaust gases leaving the unit with blowing oxygen is realized. As a result, a torch is formed above the neck of the converter. Thermal radiation from the specified torch is an additional source of heat for the converter bath, and the parameters of the torch can characterize the processes occurring in the volume of the converter. The blowing of the iron-carbon melt with oxygen is accompanied by intense smoke and dust formation, which should have a significant effect on the optical-thermal parameters of the flame of flue gases postcombustion in the oxygen converter. The paper presents the results of the study of the influence of solid particles of a sufficiently large fraction (more than 200 μm) on the heat transfer of a burning torch by radiation as the main method of heat transfer from a flame. The simulation was performed using a physical model that allowed to simulate a single volume of a burning flue gas postcombusted in a converter with the ability to measure the amount of heat transferred from it to the environment. As a result of the research, it was found that the emersion of solid particles into the burning torch leads to a change in its qualitative optical parameters: the appearance of a yellow-orange color, which indirectly indicates a decrease in the torch temperature. It was established by calculation method that, regardless of the degree of blackness of the torch, only particles with a fraction of less than 10 microns, when hitting it, can be heated to temperatures approaching the temperature of the possible onset of luminescence. Therefore, solid particles of the investigated fraction cannot participate in the total radiation of the torch. It was also noted that the effect of the size of the fraction of solid particles over 200 μm on the specific excess density of the heat flux is of a stepwise nature with a decrease in the value of the excess density of the heat flux from the torch with an increase in the size and amount of suspended solid particles in it.